Spin Isomers and Ligand Isomerization in a Three-Coordinate Cobalt(I) Carbonyl Complex - Al-Afyouni, Malik H; Suturina, Elizaveta; Pathak, Shubhrodeep; Atanasov, Mihail; Bill, Eckhard; DeRosha, Daniel E; Brennessel, William W; Neese, Frank; Holland, Patrick L (Journal of the American Chemical Society, 2015)
Hemilabile ligands, which have one donor that can reversibly bind to a metal, are widely used in transition-metal catalysts to create open coordination sites. This change in coordination at the metal can also cause spin-state changes. Here, we explore a cobalt(I) system that is poised on the brink of hemilability and of a spin-state change and can rapidly interconvert between different spin states with different structures ("spin isomers"). The new cobalt(I) monocarbonyl complex L(tBu)Co(CO) (2) is a singlet ((1)2) in the solid state, with an unprecedented diketiminate binding mode where one of the C═C double bonds of an aromatic ring completes a pseudo-square-planar coordination. Dissolving the compound gives a substantial population of the triplet ((3)2), which has exceptionally large uniaxial zero-field splitting due to strong spin-orbit coupling with a low-lying excited state. The interconversion of the two spin isomers is rapid, even at low temperature, and temperature-dependent NMR and electronic absorption spectroscopy studies show the energy differences quantitatively. Spectroscopically validated computations corroborate the presence of a low minimum-energy crossing point (MECP) between the two potential energy surfaces and elucidate the detailed pathway through which the β-diketiminate ligand "slips" between bidentate and arene-bound forms: rather than dissociation, the cobalt slides along the aromatic system in a pathway that balances strain energy and cobalt-ligand bonding. These results show that multiple spin states are easily accessible in this hemilabile system and map the thermodynamics and mechanism of the transition.